Women in India : Vedic to modern times - Gross, Susan Hill, 1934-; Bingham, Marjorie Wall, 1936- (St. Louis Park, MN : Glenhurst Publications, 1980)
Examines the historical, social, and cultural roles of women in Indi a, with an emphasis on Hindu women.
"Women in World Area Studies, an ESEA, Title IV-C Federal Project."
Includes bibliographical references ( p. 101-103.)
Keywords: Women -- India -- Social conditions -- Juvenile literature; Hindu women -- India -- Juvenile literature; Women -- India -- History -- Juvenile literature; Women -- India; Hindu women -- India